TREM2 and sTREM2 in Alzheimer’s disease: from mechanisms to therapies - Lianshuai Zhang; Xianyuan Xiang; Yahui Li; Guojun Bu; Xiao-Fen Chen (Molecular Neurodegeneration)
Abstract Triggering receptor expressed on myeloid cells 2 (TREM2) is an innate immune receptor predominantly expressed by microglia in the brain. Recent studies have established TREM2 as a central immune signaling hub in neurodegeneration, where it triggers immune responses upon sensing pathological development and tissue damages. TREM2 binds diverse ligands and activates downstream pathways that regulate microglial phagocytosis, inflammatory responses, and metabolic reprogramming. Interestingly, TREM2 exists both in its membrane-bound form and as a soluble variant (sTREM2), that latter is generated through proteolytic shedding or alternative splicing and can be detected in cerebrospinal fluid and plasma. Emerging clinical and preclinical evidence underscores the potential of TREM2 and sTREM2 as diagnostic biomarkers and therapeutic targets in Alzheimer’s disease (AD). This review provides a comprehensive overview of the molecular functions, regulatory mechanisms, and pathological implications of TREM2 and sTREM2 in AD. Furthermore, we explore their potential roles in diagnostics and therapeutics while suggesting key research directions for advancing TREM2/sTREM2-based strategies in combating AD.